Analisis Kombinasi Vigenere Cipher dengan Algoritma Rsa dalam Pengamanan Data Tekstual - Pertiwi, Luh Arimas; ER, Ngurah Agus Sanjaya; Putra, Ida Ayu Gde Suwiprabayanti; Wirawan, I Made Widhi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 14 No 1 (2025): JELIKU Volume 14 No 1, August 2025 - Preliminary Edition (Expected Completion: August 31, 2025), 2025)
Digital data security is very important to protect sensitive information, such as school savings and loan cooperatives that store member data and financial transactions. Cyber threats, such as hacking, identity theft, and data misuse, can have a negative impact on the cooperative's operations and reputation. Cryptographic algorithms are used to protect this data, cryptography consists of symmetric and asymmetric algorithms. Symmetric and asymmetric algorithms each have their advantages and disadvantages. Vigenère cipher, as a symmetric algorithm, offers encryption speed, but has weaknesses in key security, while RSA as an asymmetric algorithm is more secure, but with a slower process. To overcome the weaknesses of both algorithms, a hybrid cryptosystem that combines both algorithms can be used to provide an additional layer of security. This study aims to evaluate and compare the encryption results using the Vigenère Cipher algorithm alone with a combination of Vigenère cipher and RSA and to test the system's resistance to brute force attacks. The results of this study are expected to show that the combination of these two algorithms provides stronger protection to maintain the confidentiality of sensitive information